2022
DOI: 10.1021/acsbiomedchemau.2c00007
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Antimicrobial Activity and Mechanism of Clotrimazole-Linked CO-Releasing Molecules

Abstract: Several metal-based carbon monoxide-releasing molecules (CORMs) are active CO donors with established antibacterial activity. Among them, CORM conjugates with azole antibiotics of type [Mn(CO) 3 (2,2′-bipyridyl)(azole)] + display important synergies against several microbes. We carried out a structure−activity relationship study based upon the lead structure of [Mn(CO) 3 (Bpy)(Ctz)] + by producing clotrimazole (Ctz) conjugates with varying metal and ligands. We concluded that the nature of the bidentate ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…ranging from ca. -9 to -11 kcal/mol) are fully consistent with the experimental results reported by Wenzel et al [31] and Mendes et al [48], in that inhibition of these proteins would lead to membrane disorganization and affect peptidoglycan/wall biosynthesis [76,[80][81][82][83][84].…”
Section: Molecular Docking Study -Membrane Bound S Aureus Proteinssupporting
confidence: 90%
See 3 more Smart Citations
“…ranging from ca. -9 to -11 kcal/mol) are fully consistent with the experimental results reported by Wenzel et al [31] and Mendes et al [48], in that inhibition of these proteins would lead to membrane disorganization and affect peptidoglycan/wall biosynthesis [76,[80][81][82][83][84].…”
Section: Molecular Docking Study -Membrane Bound S Aureus Proteinssupporting
confidence: 90%
“…compound 14 in Figure 4, targets the cytoplasmic membrane of Bacillus subtilis, affecting its architecture and disrupting essential cellular processes taking place at the membrane, such as respiration, and cell wall biosynthesis and integrity [31]. Similarly Mendes et al have shown that the mechanism of action of the fac-[Re(CO)3(bpy)(ctz)] + complex (17 in Figure 4, where ctz = the drug clotrimazole) involves a sequence of events initiated by membrane insertion, followed by membrane disorganization, inhibition of peptidoglycan biosynthesis, and break down of the membrane potential [48].…”
Section: Molecular Docking Study -Membrane Bound S Aureus Proteinsmentioning
confidence: 92%
See 2 more Smart Citations
“…The few in-depth studies on the mechanism of action of metallobiotics in recent years have indicated that metal compounds are likely to affect multiple targets inside of microbes. 17,26,[112][113] This makes them well suited to avoid rapid resistance development but also increases the difficulty in narrowing down their exact mode of action. 114 On behalf of CO-ADD we invite researchers around the world to submit their (well characterized) metal complexes for antimicrobial testing to advance our collective knowledge on this promising and underexplored compound class.…”
Section: Discussionmentioning
confidence: 99%